1995
DOI: 10.1103/physrevb.52.12485
|View full text |Cite
|
Sign up to set email alerts
|

Rigorous results on a first-order phase transition in antiferromagnetic spin-1/2 coupled chains

Abstract: Some rigorous results are presented for a first-order quantum phase transition between the dimerized state and Haldane-type state (i.e., a state similar to the ground state of the one-dimensional spin-1 Heisenberg chain) in the spin-1/2 coupled chains with nearest-neighbour and next-nearestneighbour Heisenberg interactions. Also presented are the exact excited states in both phases. A partial phase diagram of the general spin-1/2 coupled chains is discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
93
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 25 publications
4
93
0
Order By: Relevance
“…Like the Shastry-Sutherland model, it exhibits a phase with a dimer-singlet ground state, fully localized triplet excitations, and a first-order phase transition [47,49]. The importance of multi-triplet bound-state excitations was also recognized in early analytical studies of the fully frustrated ladder [47,49] and observed in a DMRG calculation [52].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Like the Shastry-Sutherland model, it exhibits a phase with a dimer-singlet ground state, fully localized triplet excitations, and a first-order phase transition [47,49]. The importance of multi-triplet bound-state excitations was also recognized in early analytical studies of the fully frustrated ladder [47,49] and observed in a DMRG calculation [52].…”
Section: Introductionmentioning
confidence: 97%
“…the model of Eq. (1) with J × = J ] possesses a first-order quantum phase transition as a function of the coupling ratio J ⊥ /J [49,53]. This transition separates a rung-singlet phase for strong J ⊥ from a rung-triplet, or Haldane [3], phase at weak J ⊥ .…”
Section: Ground Statementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there are cases in which frustration causes a first-order transition in quantum spin systems in contrast to a second-order transition in the corresponding classical model (see for example Refs. [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The entire region below the transition line is in the Haldane phase, being continuously related to the point (J × /J = 1, J ⊥ /J = 0) at which the ladder is equivalent to a spin-1 chain. [3][4][5][6][7] The debate centred over the existence or not of a columnar dimer (CD) phase intermediate between the rung-singlet and Haldane phases which was predicted on the basis of weak coupling field theory renormalisation group arguments. 17 This phase is between…”
Section: Introductionmentioning
confidence: 99%